Persistent headache attributed to previous ischemic stroke: a prospective cohort study - Oliveira, Felipe Araújo Andrade de; Dourado Filho, Mario Genuíno; Rocha-Filho, Pedro Augusto Sampaio (Headache Medicine, 2022)
Introduction Headache is a frequent sign of stroke, occurring both in the acute phase and persisting for 3 months after the stroke. The most recent International Classification of Headache Disorders has included persistent headache attributed to past stroke. Diagnosis depends on the presence of headache in the acute phase of stroke, although the headache persists for more than 3 months after the cerebrovascular event. Objectives To assess the incidence, course and impact of persistent headache attributed to a past ischemic stroke. To identify risk factors for the development of persistent headache attributed to a past stroke. Methods This was a prospective, observational cohort study. Inpatients with stroke, admitted within 72 hours of the onset of symptoms, were assessed at the Real Hospital Português de Beneficência de Pernambuco. Diagnosis of ischemic stroke occurred through the presence of an area of restricted diffusion in the magnetic resonance examination within a compatible clinical context. A semi-structured questionnaire was applied to characterize the sociodemographic information, the cerebrovascular disease and the headaches according to the diagnostic criteria of the International Classification of Headache Disorders. The NIHSS Stroke Scale and the HIT-6 scale were also used. Patients were assessed in person by the researchers in the acute phase of stroke and by telephone after 1 year to assess persistent headache attributed to past stroke. Results Initially, 221 patients were included, most of them male (59.3%) and whose mean age was 68.2 years ± 13.8. One hundred and nineteen patients (53.9%) answered the questionnaire by telephone 1 year after the stroke. Persistent headache attributed to a past stroke presented a frequency of 10.1% in the sample (95%CI: 5.3 to 17.0%) 1 year after the stroke. Headache presented a median frequency of 2.5 (1 – 4) days... (To see the complet abstract, please, check out the PDF.)